- RESTRUKTURISASI KREDIT USAHA RAKYAT KECIL DI MASA PANDEMI COVID-19 DITINJAU DARI PRINSIP KEHATI-HATIAN (STUDI KASUS BANK BRI KCP SRIWIJAYA MATARAM): - - Fiona Khairunnisa; Setyaningsih (Reformasi Hukum Trisakti, 2023)
During the COVID-19 pandemic, the Government implemented relaxation rules as a National Economic Recovery ("PEN") for People's Business Credit ("KUR") debtors which are regulated in POJK 11/2020 and Permenko Perekonomian 19/2020, one of BRI KCP Sriwijaya's Small KUR debtor customers who received credit relaxation and failed to restructure will be reviewed from the Prudential Principles. The formulation of the problem discussed, how is the implementation of KUR relaxation at BRI KCP Sriwijaya Mataram during the COVID-19 pandemic in terms of the Prudential Principles of the Banking Law and whether there are obstacles for BRI KCP Sriwijaya Mataram in implementing Small KUR relaxation during the COVID-19 Pandemic in terms of Prudential Principles. The research method used is normative, analytical descriptive research nature and the type of data used is secondary data supported by primary data, qualitative analysis with deductive inference. The conclusion in this study is that default is caused by the non-fulfillment of the Capacity aspect of both the debtor and the bank in predicting the business prospects of Small KUR debtors and BRI KCP Sriwijaya Mataram debtors, the majority of whom have businesses in the tourism sector.